Goodbye to Grand Politics: The Cane Sugar Campaign and the Limits of Transnational Activism, 1968–1974. (November 2019) - van Dam, Peter
Abstract: In 1968 Dutch activists launched a campaign focused on cane sugar as a symbol of unfair trading conditions for the global South. The history of the cane sugar campaign from 1968 to 1974 highlights how European integration provided hope for large-scale change and a common target. This led activists to establish European networks and campaigns. Its demise sheds new light on the new social movements' shift from 'grand politics', aimed at a sudden and drastic transformation through global and European politics, towards incremental change by locally targeting specific companies and countries.